The 26th Annual International Conference of the IEEE Engineering in Medicine and Biology Society
DOI: 10.1109/iembs.2004.1404158
|View full text |Cite
|
Sign up to set email alerts
|

Sputtered iridium oxide films (SIROFs) for low-impedance neural stimulation and recording electrodes

Abstract: Sputtered iridium oxide films (SIROFs) deposited by DC reactive sputtering from an iridium metal target have been characterized in vitro for their potential as neural recording and stimulation electrodes. SIROFs were deposited over gold metallization on flexible multielectrode arrays fabricated on thin (15 µm) polyimide substrates. SIROF thickness and electrode areas of 200-1300 nm and 1960-125600 µm 2 , respectively, were investigated. The charge-injection capacities of the SIROFs were evaluated in an inorgan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 11 publications
5
76
0
Order By: Relevance
“…A similar approach using non-toxic components during film formation has been introduced by Zhou 2005, known as Pt gray, however the roughness was found substantially lower compared to Pt-black [20]. Cui et al [21] and Cogan et al [22] demonstrated successfully the reduction of the electrode impedance using either conducting M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT polymers as e.g. poly(3,4-ethylenedioxythiophene) (PEDOT) or using Iridium Oxide (IrOx) targeting both the chemical and the topographical approach to improve the electrode performance.…”
Section: Introductionmentioning
confidence: 97%
“…A similar approach using non-toxic components during film formation has been introduced by Zhou 2005, known as Pt gray, however the roughness was found substantially lower compared to Pt-black [20]. Cui et al [21] and Cogan et al [22] demonstrated successfully the reduction of the electrode impedance using either conducting M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT polymers as e.g. poly(3,4-ethylenedioxythiophene) (PEDOT) or using Iridium Oxide (IrOx) targeting both the chemical and the topographical approach to improve the electrode performance.…”
Section: Introductionmentioning
confidence: 97%
“…One of the popular electrode materials, sputtered iridium oxide (SIROF), can deliver up to 5 mC/cm 2 via an electrode of 30 m in diameter, with the use of 0.5-ms pulses (Cogan et al 2004). These settings correspond to the maximum current of 70 A, which is 16 -175 times higher than the stimulation lower threshold at this pulse duration, and can significantly exceed the stimulation upper threshold.…”
Section: Computational Modeling Of Extracellular Stimulationmentioning
confidence: 99%
“…The strength-duration relationship defines for a given pulse duration the minimum stimulus strength, or stimulation threshold, above which an action potential (AP) is generated. It is generally assumed that a neuron will elicit AP at any stimulus strength above the threshold, and the upper limit is defined only by the cellular damage (Butterwick et al 2007;McCreery et al 1990) or by the limits of irreversible electrochemistry on stimulating electrode (Brummer and Turner 1977;Cogan et al 2004).…”
mentioning
confidence: 99%
“…9 However, PEDOT and other conjugated polymers, including polypyrrole and polyaniline, are non-biodegradable and brittle. 10 In certain tissues, such as the heart, conjugated polymers could cause adverse immune responses upon implantation, as the ischemic myocardium is a hostile environment where inflammatory responses can perpetuate the scarring. 11 .…”
Section: Introductionmentioning
confidence: 99%